Improving Students' Speaking Skills Through Digital Storytelling at Islamic Schools: A Systematic Literature Review - Nasywa Kamilah; Marini Putri; Naf’an Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
Digital storytelling (DST), which combines narrative creation with multimedia elements such as images, audio, and video, has emerged as an engaging strategy to enhance speaking skills in EFL contexts. In Islamic schools, DST offers a platform for learners to communicate creatively while integrating moral, cultural, and faith-based values, reflecting the principles of Islamic education. Despite its promise, students often face challenges in speaking, including limited fluency, weak pronunciation, narrow vocabulary, and low confidence. This review systematically examines how DST supports speaking development in Islamic school settings. Using a structured literature review methodology, relevant studies were collected from databases such as Google Scholar, Scopus, and ERIC, applying strict inclusion criteria focused on speaking outcomes, school-aged learners, and DST implementation. Thematic analysis revealed that DST improves fluency, pronunciation accuracy, vocabulary use, narrative coherence, and overall oral performance. It also enhances motivation, reduces speaking anxiety, and fosters willingness to communicate by providing opportunities for creative rehearsal and collaborative storytelling. Additionally, DST enables students to express culturally and ethically relevant ideas, supporting character-building in line with Islamic values. Challenges include digital literacy gaps and the need for teacher guidance. Overall, DST is an effective pedagogical tool for developing speaking skills in Islamic school contexts, provided sufficient technological support and structured instructional scaffolding are in place